Threshold effect of ecosystem services in response to climate change and vegetation coverage change in the Qinghai-Tibet Plateau ecological shelter. (10th October 2021) - Ma, Shuai; Wang, Liang-Jie; Jiang, Jiang; Chu, Lei; Zhang, Jin-Chi
Abstract: Understanding the impacts of climate change and vegetation restoration on ecosystem services is essential for sustainable ecosystem management. However, the characteristics of nonlinear impacts of climate change and vegetation change on ecosystem services are still unclear, especially the determination of their impact thresholds. The Qinghai-Tibet Plateau ecological shelter (QPES) was chosen as the study area. The changes in precipitation, temperature, fractional vegetation cover (FVC) and ecosystem services (water yield, net primary productivity (NPP) and soil conservation) were analyzed, the impacts of climate and vegetation cover changes on ecosystem services were evaluated, and the thresholds were quantitatively identified. The results showed that annual mean precipitation increased from 2000 to 2014 and dropped sharply in 2015, with temperatures rising significantly (p < 0.05) and vegetation recovering significantly (p < 0.01) from 2000 to 2015. NPP showed a fluctuating and rising trend from 2000 to 2015. Water yield and soil conservation were greatly affected by precipitation. NPP and soil conservation increased as vegetation improved. The impact threshold of precipitation on ecosystem services was 533 mm. When the annual mean temperature higher than −3.44 °C, the positive impact on ecosystem services was weakened; when it higher than 1.98 °C, the impact on ecosystem services was negative. The FVC thresholds in the study region and in the alpine steppe zone, alpine forest zone, alpine meadow zone, subtropical coniferous forest zone, alpine desert zone and temperate desert zone were 0.61, 0.37, 0.67, 0.53, 0.65, 0.20 and 0.24, respectively. This study provides an important reference for large-scale ecological management and moderate restoration. Graphical abstract: Image 1 Highlights: The trends of ecosystem services over a long time series were analyzed. Ecosystem services showed fluctuation changes, and drivers may be unstable. Impacts of climate and vegetation cover changes on ecosystem services were non-linear. FVC thresholds can be incorporated into ecological restoration policy thresholds. Sustainable ecosystem management requires appropriate restoration of vegetation.